BLOOD PRESSURE IN A POPULATION OF A RURAL AREA OF RWANDA: PRELIMINARY DATA. (April 2021) - Muggli, Franco; Parati, Gianfranco; Suter, Paolo; Bianchetti, Mario; Radovanovic, Dragana; Umulise, Alice; Muvunyi, Bienvenu; Ntaganda, Evariste
Abstract : Objective: Arterial hypertension likely affects millions of people in Africa and is the most important cause of heart disease and stroke. In Sub-Saharan Africa, the burden of hypertension is a rapid growing health threat. The objective of our study was to perform a screening of the local population living in the rural area of the District of Nyaruguru (Rwanda) to determine the prevalence of high blood pressure (BP). Design and method: Between February and July 2020, instructed health care workers collected some anthropometric data (such as height and weight) and measured BP three times in sitting position with validated oscillometric device (OMRON HEM-7322U). Results: A total of 7336 subjects participated to the screening, with median age of 32 (IQR 21, 47) years; 4053 (55%) were female, age 35 (23, 49) years; 3283 (45%) were male, age 30 (20, 44) years (p < 0.001). Body Mass Index was 20.7 (19.0, 22.3) in males and 21.8 (20.0, 23.8) in females (p < 0.001). The mean of the last two BP measurements were 119.5 ± 15.2 mm Hg. Males had a higher systolic blood pressure (SBP) 120.1 ± 14.0 mm Hg comparing to female 118.6 ± 16.1 (p < 0.001.) Considered SBP equal or more than 140 mm Hg for the diagnosis of hypertension 642 subjects (8.8%) had high BP values, without differences between males (8.4%) und female (9.0%); p = 0.36. Conclusions: Surprisingly, in a very rural peripheral region where the average age of the inhabitants is relatively low, about 9% of the subjects examined have abnormal BP values. These data confirm the need to implement also in rural areas of Rwanda an adequate strategy for the prevention, diagnosis and treatment of hypertension.